Implementasi Media Teka Teki Silang Dalam Upaya Meningkatkan Pengetahuan dan Sikap Remaja Putri Tentang Anemia di SMK Karsa Mulya Palangka Raya - Rayani Purba, Lidya Sarma; Susanti, Nila; Mashar, Harlyanti Muthma'innah (Politeknik Negeri Jember, 2023)
Adolescent women are particularly susceptible to anemia caused by significant blood loss during menstruation phase. Another factor that could cause anemia are lack of knowledge and intake of iron. The education using crossword puzzles to increase knowledge can be used to prevent anemia in adolescent women. This study aimed to determine the effect of crossword puzzles on the level of knowledge and attitudes of young women about anemia at SMK Karsa Mulya Palangka Raya. The type of research used a Quasi-experimental research design with one group pre-posttest design without a control group. The sample in this study was female students at SMK Karsa Mulya Palangka Raya, totaling 45 people. The respondent was given a pretest questionnaire, being educated using a crossword puzzle twice for four weeks, and a posttest to evaluate the education results. Data analysis for knowledge used Wilcoxon test and attitudes used paired t-tests. The results showed that the majority of respondents were 15-18 years old, and the highest prevalence respondent was 15 years old (42.2%). The analysis showed that crossword puzzles significantly affect adolescent women's knowledge levels and attitudes (p=0.000) about anemia at SMK Karsa Mulya Palangka Raya. Keywords: Anemia, Attitudes, Crossword, Knowledge